Kalıcı hemodiyaliz kateterleri: Ne kadar kalıcı? - (:unkn) unknown (My University, 2013)
Amaç: Bu çalışmada kalıcı hemodiyaliz kateterlerinin takılmasında en uygun ve güvenilir yöntemler, bu yöntemlerin komplikasyonları ve kateterlerin açıklık oranları değerlendirildi. Çal ışm a planı: Ocak 2008 - Haziran 2012 tarihleri arasında kliniğimizde kalıcı hemodiyaliz kateteri takılan ve halen hastanemiz hemodiyaliz ünitesinde hemodiyaliz programında olan 127 hasta (72 erkek, 55 kadın; ort. yaş 65.0±14.7 yıl; dağılım 17-85 yıl) retrospektif olarak değerlendirildi. Hastaların yaşı ve cinsiyeti, kateterlerin takılma endikasyonları, takılma yerleri, çıkarılma nedenleri, kullanım süreleri ve katetere bağlı komplikasyonlar kaydedildi. Kateter ömrü, kateterin takıldığı tarihten katetere bağlı gelişen komplikasyonlardan dolayı çıkarıldığı tarihe kadar geçen süre olarak tanımlandı. Bulgular: Yüz yirmi yedi hastaya toplam 155 adet kalıcı hemodiyaliz kateteri yerleştirildi. Kateterlerin 79u sağ juguler ven, 22si sol juguler ven, 13ü sağ subklaviyan ven, sekizi sol subklaviyan ven, beşi sağ femoral venden yerleştirildi. Kateterler yedi hastada enfeksiyon, 13 hastada kateter içi tromboz, beş hastada kateter malpozisyonu, üç hastada ise diğer nedenlerle yeni bir kalıcı kateter ile değiştirildi. Sonuç: Kalıcı hemodiyaliz kateterlerinin kullanım süresi uygun kateter seçimi, uygun kateter giriş yeri, klinisyenin deneyimi ve işlemin ultrasonografi veya floroskopi kılavuzluğunda yapılması ile doğrudan iliş- kilidir.

Background: In this article, we evaluated the most appropriate and safest methods to insert permanent hemodialysis catheters, the complications of these methods and catheter patency rates. Methods: Between January 2008 and June 2012, 127 patients (72 males, 55 females; mean age 65.0±14.7 years; range, 17 to 85 years) in whom a permanent hemodialysis catheter was inserted in our clinic and who continued to undergo hemodialysis program in the hemodialysis unit of our hospital were retrospectively analyzed. Age and sex of the patients, indication for catheter insertion, the localization, reasons for catheter removal, duration of use and catheter-related complications were recorded. Life of the catheter was defined as the period of time from the date in which the catheter was inserted to the date in which the catheter was removed due to catheter-related complications. Results: A total of 155 permanent hemodialysis catheters were inserted to 127 patients. Seventy-nine were inserted via the right jugular vein, 22 via the left jugular vein, 13 via the right subclavian vein, eight via the left subclavian vein, five via right femoral vein. A new permanent catheter was inserted due to infection in seven patients, due to catheter thrombosis in 13 patients, catheter malposition in five patients, and other complications in three patients. Conclusion: The duration of use of a permanent hemodialysis catheter is directly related to an appropriate catheter choice, appropriate localization for insertion, experience of the clinician and with the guidance of ultrasonography or fluoroscopy.
Permanent hemodialysis catheters: How long lasting are they?
Keywords: Kalp ve Kalp Damar Sistemi; Cerrahi